2021
DOI: 10.4081/ijfs.2021.9332
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ionophore and non-ionophore anticoccidials residues in poultry meat and eggs and their risk characterization

Abstract: A multi-residue method was applied to investigate the incidence and the concentration of ionophores and non-ionophore anticoccidials residues in poultry meat and hen eggs for the three-year period 2017-2019 in Italy. The risk related to the ingestion of such molecules was also characterized for the entire population. The average incidences of positive samples ranged from 1.35 to 9.45% while the maximum average concentration was of 4.28 μg/kg for nonionophore molecules. No uncompliant sample was recorded. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…T A B L E 4 Method validation parameters: accuracy (as percentage mean recovery), precision (as intra-day repeatability CV% and inter-day repeatability CV%), and expanded uncertainty for all the investigated coccidiostats at two levels of concentration (2.00 and 20.0 μg/kg) in white meat.necessary also at a concentration lower than the established MRLs.Our results are in agreement with Roila et al 2021 that analyzed the results of the Italian official residues control plans in the period 2017-2019 concluding the absence of actual risk for consumers but suggesting continuous monitoring plans in order to safeguard consumer's health 1. DIC was found in the other 40% of positive meat samples analyzed by our laboratory at a minimum concentration value of 8.6 μg/ kg in rabbit muscle and a maximum of 626 μg/kg in rabbit liver.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…T A B L E 4 Method validation parameters: accuracy (as percentage mean recovery), precision (as intra-day repeatability CV% and inter-day repeatability CV%), and expanded uncertainty for all the investigated coccidiostats at two levels of concentration (2.00 and 20.0 μg/kg) in white meat.necessary also at a concentration lower than the established MRLs.Our results are in agreement with Roila et al 2021 that analyzed the results of the Italian official residues control plans in the period 2017-2019 concluding the absence of actual risk for consumers but suggesting continuous monitoring plans in order to safeguard consumer's health 1. DIC was found in the other 40% of positive meat samples analyzed by our laboratory at a minimum concentration value of 8.6 μg/ kg in rabbit muscle and a maximum of 626 μg/kg in rabbit liver.…”
supporting
confidence: 93%
“…For these reasons, the monitoring of coccidiostats residue in meat supply chain products become necessary also at a concentration lower than the established MRLs. Our results are in agreement with Roila et al 2021 that analyzed the results of the Italian official residues control plans in the period 2017–2019 concluding the absence of actual risk for consumers but suggesting continuous monitoring plans in order to safeguard consumer's health 1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the result of the yearly reports on the monitoring of veterinary medicinal products residues and other substances in live animals and animal products conducted by the EFSA from 2010 to 2019 across the EU, the number of non-compliant results for targeted and suspected egg samples obtained for registered coccidiostats revealed that ionophore coccidiostats were the most frequent coccidiostat feed additives found to contaminate laying eggs ( Figure 1 ; EFSA, 2012 , EFSA, 2013 , EFSA, 2014 , EFSA, 2015 , EFSA, 2016 , EFSA, 2017 , EFSA, 2018 , EFSA, 2019 , EFSA, 2020 , EFSA, 2021 ). Among the authorized ionophore coccidiostats, lasalocid was consistently detected as the most common coccidiostat residue in eggs ( Mortier et al, 2005 ; Olejnik et al, 2011 ; Pia̧tkowska et al, 2012 ; Roila et al, 2021 ). This is supported by the result of the yearly report of EFSA from 2010 to 2019 on the monitoring of veterinary medicinal products residues and other substances in live animals and animal products where lasalocid is characterized by a fluctuating yearly incidence of occurrence along the time frame considered and it appeared to have the highest frequency of occurrence in the non-compliant samples of commercial poultry eggs as shown in Figure 2 ( EFSA, 2012 , EFSA, 2013 , EFSA, 2014 , EFSA, 2015 , EFSA, 2016 , EFSA, 2017 , EFSA, 2018 , EFSA, 2019 , EFSA, 2020 , EFSA, 2021 ).…”
Section: Sources Of Exposure In Laying Hens and Incidence Of Occurren...mentioning
confidence: 99%
“…Despite the restriction on the use of ionophore coccidiostats in the production management of laying hens, it was observed that they are the non-target species of poultry being most frequently exposed to such feed additives ( Kennedy et al, 1998 ; Olejnik et al, 2011 ; Chapman, 2017 ). Moreover, non-compliant egg samples containing violative residues of ionophore coccidiostats are still being reported by regulatory authorities ( EFSA, 2021 ; Roila et al, 2021 ). The number of egg samples that must be collected for the monitoring of ionophore coccidiostats in commercial poultry eggs must be at least equal to one sample per 1,000 tonne of annual egg production, with a minimum of 200 samples required to be collected each year, depending on the volume of egg production in each EU member state.…”
Section: Introductionmentioning
confidence: 99%